Titanium alloy surface antifouling corrosion-resistant coating as well as preparation method and application thereof

By using titanium-based composite powder and laser cladding technology on the surface of titanium alloy, the problem of titanium alloy being susceptible to pollution and corrosion in the marine environment is solved, and significant corrosion resistance and anti-fouling performance are improved.

CN119553270APending Publication Date: 2025-03-04SUN YAT SEN UNIV +1

Patent Information

Application Number
CN202411785460.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Titanium alloys are susceptible to microscopic and macroscopic deficient organisms in the marine environment, resulting in biological deficiencies, limiting their application in marine engineering equipment. At the same time, the high salt and electrical conductivity of the marine environment also aggravates the corrosion risk of materials.

Method used

Anti-fouling corrosion-resistant coating prepared by titanium-based composite powder is deposited on the surface of titanium alloy through laser cladding technology, and copper elements are introduced to change the phase composition and microstructure of the alloy, promote the formation of the β phase, and improve the density and uniformity of the coating.

Benefits of technology

It significantly improves the corrosion resistance and anti-fouling capability of the titanium alloy surface, extends the service life of the equipment, reduces maintenance costs, and improves the reliability and safety of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553270A_ABST
    Figure CN119553270A_ABST
Patent Text Reader

Abstract

The invention provides a titanium alloy surface antifouling corrosion-resistant coating as well as a preparation method and application thereof. The antifouling and corrosion-resistant coating on the titanium alloy surface is prepared from raw materials including titanium-based composite powder, the titanium-based composite powder comprises titanium alloy powder and copper powder, the content of the titanium alloy powder in the titanium-based composite powder is 93 wt%-97 wt%, and the content of the copper powder in the titanium-based composite powder is 3 wt%-7 wt%. Through introduction of the copper element, the phase composition and microstructure of the alloy can be changed, formation of a beta phase is promoted, the ratio of an alpha phase to the beta phase is changed, the compactness and uniformity of a coating are effectively improved, and the corrosion resistance of the surface of the titanium alloy is remarkably improved. The invention further provides a preparation method and application of the antifouling and corrosion-resistant coating on the titanium alloy surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antifouling coatings, and specifically relates to an antifouling and corrosion-resistant coating on the surface of a titanium alloy, and a preparation method and application thereof. Background Art

[0002] Titanium alloys have the advantages of high specific strength, high toughness, and non-magnetic properties. They are known as "marine metals" and have been widely used in marine engineering equipment in recent years. However, the good biocompatibility of titanium alloys makes them susceptible to microscopic and macroscopic fouling organisms in the marine environment, such as bacteria, microalgae, and large fouling organisms. These fouling organisms attach and reproduce on their surfaces, forming biofouling, which greatly limits the application of titanium alloy engineering equipment in the marine environment.

[0003] In order to meet the challenges of biofouling to marine activities, researchers have proposed a variety of antifouling strategies, including self-polishing antifouling coatings, fouling-releasing antifouling coatings and new antifouling coatings. However, these methods mainly rely on chemical reactions to bond antifouling coatings to the substrate surface. In the complex marine environment, this bonding method is easily affected by environmental factors, resulting in performance degradation and failure of antifouling coatings, which makes traditional antifouling coatings face many challenges in long-term use. In addition, the ocean is a natural extremely complex environment. Seawater has a high salt content and strong conductivity. It is a natural highly corrosive medium. When engineering equipment made of titanium alloy is in service in the ocean, it is easy to cause damage to the surface passivation film, increasing the risk of local corrosion of the material.

[0004] Therefore, there is an urgent need to develop an anti-fouling and corrosion-resistant coating with high efficiency and strong stability to ensure the reliability and durability of marine engineering equipment. Summary of the invention

[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention provides an antifouling and corrosion-resistant coating on the surface of a titanium alloy, which has excellent antifouling and corrosion-resistant properties and can be used in marine engineering equipment to provide ideal reliability and durability.

[0006] The invention also provides a method for preparing the antifouling and corrosion-resistant coating on the surface of the titanium alloy.

[0007] The invention also provides application of the antifouling and corrosion-resistant coating on the surface of titanium alloy in marine engineering equipment.

[0008] The first aspect of the present invention provides an anti-fouling and corrosion-resistant coating on the surface of a titanium alloy. The preparation raw materials include a titanium-based composite powder, and the titanium-based composite powder includes a titanium alloy powder and a copper powder. In terms of mass percentage, the content of the titanium alloy powder in the titanium-based composite powder is 93wt% to 97wt%, and the content of the copper powder in the titanium-based composite powder is 3wt% to 7wt%.

[0009] One of the technical solutions of the present invention for the antifouling and corrosion-resistant coating on the surface of titanium alloy has at least the following characteristics:

[0010] Beneficial effects:

[0011] The present invention utilizes laser cladding modification technology to deposit a layer of antifouling and corrosion-resistant coating on the titanium alloy surface. The coating is formed by titanium-based composite powder prepared from titanium alloy powder and copper powder, and a modified metal surface with excellent antifouling and corrosion resistance can be obtained. The present invention introduces copper elements to change the phase composition and microstructure of the alloy, promote the formation of β phase, change the ratio of α phase and β phase, effectively improve the density and uniformity of the coating, and significantly improve the corrosion resistance of the titanium alloy surface. Specifically:

[0012] Different from the prior art which generally prepares microstructure on the surface of titanium alloy matrix to make titanium alloy corrosion-resistant, the present invention introduces copper element to change the phase composition and microstructure of titanium alloy, promote the formation of β phase, and adjust the ratio of α phase to β phase, so as to make the coating grains finer and more uniform, reduce the formation of defects, pores and cracks, thereby effectively optimizing the density and uniformity of the coating, and finally significantly improving the corrosion resistance of the titanium alloy surface.

[0013] Furthermore, the copper element introduced by the present invention has natural antibacterial properties and can effectively inhibit and kill a variety of bacteria, fungi and other microorganisms. Copper ions can destroy the cell walls and cell membranes of microorganisms, causing the leakage of cell contents, thereby inhibiting their growth and reproduction. This property enables the copper-doped coating to reduce the formation of bacteria and biofilms in the marine environment, reducing the risk of biofouling.

[0014] According to some embodiments of the present invention, the particle size of the titanium alloy powder is 40 to 150 μm.

[0015] According to some embodiments of the present invention, the particle size of the titanium alloy powder is any value of 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or a range formed by any two of them, such as 50-140μm.

[0016] According to some embodiments of the present invention, the copper powder has a particle size of 40 to 150 μm.

[0017] According to some embodiments of the present invention, the particle size of the copper powder is any value of 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or a range formed by any two of them, such as 50-140μm.

[0018] According to some embodiments of the present invention, the titanium alloy powder includes a powder containing a β-phase titanium alloy, or a dual-phase titanium alloy powder containing an α-phase titanium alloy and a β-phase titanium alloy.

[0019] The titanium alloy powder includes powder containing β-phase titanium alloy, or dual-phase titanium alloy powder containing α-phase titanium alloy and β-phase titanium alloy, which can promote the formation of β-phase, change the ratio of α-phase and β-phase, and ultimately effectively improve the density and uniformity of the coating, and improve the corrosion resistance of the titanium alloy surface.

[0020] The second aspect of the present invention provides a method for preparing an anti-fouling and corrosion-resistant coating on the surface of a titanium alloy according to the first aspect of the present invention, comprising the step of laser cladding the titanium-based composite powder on the surface of a titanium alloy substrate.

[0021] The present invention relates to a technical solution in a method for preparing an antifouling and corrosion-resistant coating on a titanium alloy surface, which has at least the following characteristics:

[0022] Beneficial effects:

[0023] Compared with traditional antifouling technologies, laser cladding modification technology achieves metallurgical bonding through high-energy-density lasers, which can significantly improve the adhesion between the coating and the substrate, and effectively enhance the long-term application of the coating in the marine environment. Specifically:

[0024] The present invention applies titanium-based composite powder prepared from titanium alloy powder and copper powder to a laser cladding process, thereby obtaining a dense and uniform coating on the surface of the titanium alloy substrate. This coating can effectively improve the corrosion resistance of the titanium alloy, and especially after containing copper elements, the corrosion resistance of the coating is significantly improved.

[0025] The preparation method of the present invention changes the phase composition of the titanium alloy by introducing the copper element, promotes the formation of the β phase, and adjusts the ratio of the α phase to the β phase. The addition of copper makes the grains in the coating more refined, and the uniformity and density are also improved. This optimized microstructure reduces the formation of defects, pores and cracks, thereby improving the overall performance of the coating.

[0026] Furthermore, the preparation method of the present invention effectively optimizes the density and uniformity of the titanium alloy coating by changing the phase composition and microstructure of the alloy, which not only improves the corrosion resistance of the coating, but also enhances the mechanical properties of the coating and prolongs the service life of the coating.

[0027] It should also be noted that the laser cladding process can efficiently deposit titanium-based composite powders onto the surface of titanium alloy substrates, and is simple to operate and has high processing accuracy. Compared with traditional coating technology, laser cladding technology can better control the thickness and quality of the coating, and does not require complex post-processing.

[0028] Therefore, the preparation method of the present invention not only significantly improves the corrosion resistance and anti-fouling ability of the titanium alloy surface, but also enhances its stability and reliability in long-term use by improving the structure and quality of the coating.

[0029] According to some embodiments of the present invention, the titanium alloy matrix includes a titanium alloy matrix containing a β phase, or a dual-phase titanium alloy matrix containing an α phase and a β phase.

[0030] The titanium alloy matrix includes a titanium alloy matrix containing a β phase, or a dual-phase titanium alloy matrix containing an α phase and a β phase, which can promote the formation of the β phase, change the ratio of the α phase and the β phase, and ultimately effectively improve the density and uniformity of the coating, and enhance the corrosion resistance of the titanium alloy surface.

[0031] According to some embodiments of the present invention, the titanium alloy powder and the titanium alloy substrate are of the same grade, which can make the bonding strength between the coating and the substrate stronger.

[0032] According to some embodiments of the present invention, the method for preparing the titanium-based composite powder comprises the step of mixing and ball-milling the titanium alloy powder and the copper powder according to a proportion under a protective atmosphere.

[0033] According to some embodiments of the present invention, the ball-to-material ratio of the ball milling is 3 to 6:1.

[0034] According to some embodiments of the present invention, the ball-to-material ratio of the ball milling is 4 to 6:1.

[0035] According to some embodiments of the present invention, the ball-to-material ratio of the ball milling is 5:1.

[0036] According to some embodiments of the present invention, the ball milling time is 100 min to 200 min.

[0037] According to some embodiments of the present invention, the ball milling time is any value among 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min or a range formed by any two of them, such as 140 min to 160 min.

[0038] According to some embodiments of the present invention, the rotation speed of the ball mill is 100 rpm to 200 rpm.

[0039] According to some embodiments of the present invention, the rotation speed of the ball mill is any value of 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm, 2000rpm or a range formed by any two of them, such as 140rpm to 160rpm.

[0040] According to some embodiments of the present invention, the powder feeding method of laser cladding includes coaxial powder feeding or axial powder feeding.

[0041] According to some embodiments of the present invention, the powder feeding rate of the laser cladding is 0.5 r / min to 4.5 r / min.

[0042] According to some embodiments of the present invention, the powder feeding rate of the laser cladding is any value among 0.5r / min, 1.0r / min, 1.5r / min, 2.0r / min, 2.5r / min, 3.0r / min, 3.5r / min, 4.0r / min or a range formed by any two of them, such as 2.0r / min to 3.0r / min.

[0043] According to some embodiments of the present invention, the laser power of the laser cladding is 1200W to 1800W.

[0044] According to some embodiments of the present invention, the laser power of the laser cladding is any value among 1300W, 1400W, 1500W, 1600W, 1700W, 1800W or a range formed by any two of them, such as 1400W to 1600W.

[0045] According to some embodiments of the present invention, the scanning rate of the laser cladding is 6 mm / s to 10 mm / s.

[0046] According to some embodiments of the present invention, the scanning rate of the laser cladding is any one of 6 mm / s, 7 mm / s, 8 mm / s, 9 mm / s, 10 mm / s or a range formed by any two of them, such as 7 mm / s to 9 mm / s.

[0047] According to some embodiments of the present invention, the method further comprises the step of pretreating the surface of the titanium alloy substrate before performing laser cladding.

[0048] According to some embodiments of the present invention, the pre-processing step comprises:

[0049] The titanium alloy surface was polished by hand-held vibrating sandpaper machine (SiC sandpaper) to remove surface oil and oxide layer. The polishing step was ended with 800-mesh sandpaper. The substrate surface was cleaned with anhydrous ethanol and dried for later use.

[0050] The third aspect of the present invention provides the use of the anti-fouling and corrosion-resistant coating on the surface of the titanium alloy according to the first aspect of the present invention in marine engineering equipment.

[0051] The present invention provides a technical solution for the application of anti-fouling and corrosion-resistant coating on the surface of titanium alloy in marine engineering equipment, which has at least the following beneficial effects:

[0052] 1. Excellent seawater corrosion resistance. Seawater in the marine environment contains high concentrations of salt and a variety of corrosive substances. Titanium alloys themselves have good corrosion resistance, but in harsh marine environments, the risk of corrosion of titanium alloys still exists. By applying anti-fouling and corrosion-resistant coatings on the surface of titanium alloys, especially titanium-based composite powder coatings with copper elements, their resistance to seawater corrosion can be further improved. The density and uniformity of the coating can effectively prevent the penetration of salt water and other corrosive media, thereby reducing the corrosion problems of marine engineering equipment and extending the service life of the equipment.

[0053] 2. Antifouling performance. Dirt, seaweed, microorganisms and other biological attachments in the marine environment often adhere to the surface of marine engineering equipment, causing the surface performance of the equipment to deteriorate and even affecting the operating efficiency of the equipment. The antifouling coating changes the microstructure of the titanium alloy surface to make its surface more resistant to adhesion. The surface of the coating can reduce the contact force between biological attachments and the metal surface, reduce the accumulation of attachments, thereby keeping the equipment surface clean and smooth, and helping to reduce cleaning and maintenance costs.

[0054] 3. Improve the reliability and safety of equipment. In marine engineering, equipment is usually faced with long-term high-intensity working conditions and complex environmental factors. After the titanium alloy surface is protected by anti-fouling and corrosion-resistant coating, it can effectively reduce the risk of failure caused by corrosion and biological adhesion. The excellent performance of the coating improves the reliability of the equipment, reduces the maintenance frequency and downtime, and ensures the safe operation of the equipment in the marine environment.

[0055] 4. Reduce maintenance costs. Marine engineering equipment such as ships, platforms, and submarine pipelines are exposed to seawater for a long time and will be affected by corrosion and biological attachment, requiring frequent maintenance and cleaning. After using titanium alloy surface anti-fouling and corrosion-resistant coating, the equipment surface is easier to keep clean, and the accumulation of corrosion and attachments is effectively controlled, thereby reducing the frequency of repairs and cleaning and significantly reducing maintenance costs.

[0056] 5. Enhance long-term stability and environmental adaptability. The temperature, humidity, tides, surges, etc. in the marine environment are changeable, and marine engineering equipment needs to have strong environmental adaptability. The high density and uniformity of the anti-fouling and corrosion-resistant coating on the surface of titanium alloy enables it to maintain stable performance during long-term use, resist the severe test of the marine environment, and further enhance the adaptability and long-term stability of titanium alloy in complex environments.

[0057] Therefore, the application of the titanium alloy surface anti-fouling and corrosion-resistant coating of the present invention in marine engineering equipment can significantly improve the corrosion resistance of the equipment, reduce dirt adhesion, extend the service life, improve the reliability and safety of the equipment, and reduce maintenance costs. It also has good environmental adaptability and sustainability, and is an effective solution to improve equipment performance, reduce maintenance costs, and extend service life in the field of marine engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 is the element distribution diagram of the example sample.

[0059] Figure 2 It is the X-ray diffraction test results of the examples and comparative examples.

[0060] Figure 3 It is the microhardness test result of the example and comparative example samples.

[0061] Figure 4 is the equivalent circuit diagram.

[0062] Figure 5 It is the polarization curve diagram of the embodiment and the comparative example sample.

[0063] Figure 6 1 is a bacterial adhesion diagram of the examples and comparative examples.

[0064] Figure 7 It is a schematic diagram of the antifouling mechanism of the coating.

[0065] Figure 8 It is the absorbance test result of embodiment and comparative example sample. DETAILED DESCRIPTION

[0066] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0067] In the first aspect, some embodiments of the present invention provide an anti-fouling and corrosion-resistant coating on the surface of a titanium alloy, wherein the raw materials for preparing the coating include a titanium-based composite powder, the titanium-based composite powder includes a titanium alloy powder and a copper powder, and in terms of mass percentage, the content of the titanium alloy powder in the titanium-based composite powder is 93wt% to 97wt%, and the content of the copper powder in the titanium-based composite powder is 3wt% to 7wt%.

[0068] It should be noted that the present invention utilizes laser cladding modification technology to deposit a layer of antifouling and corrosion-resistant coating on the titanium alloy surface. The coating is formed by titanium-based composite powder prepared from titanium alloy powder and copper powder, and a modified metal surface with excellent antifouling and corrosion resistance can be obtained. The present invention introduces copper elements to change the phase composition and microstructure of the alloy, promote the formation of β phase, change the ratio of α phase and β phase, effectively improve the density and uniformity of the coating, and significantly improve the corrosion resistance of the titanium alloy surface. Specifically:

[0069] Different from the prior art which generally prepares microstructure on the surface of titanium alloy matrix to make titanium alloy corrosion-resistant, the present invention introduces copper element to change the phase composition and microstructure of titanium alloy, promote the formation of β phase, and adjust the ratio of α phase to β phase, so as to make the coating grains finer and more uniform, reduce the formation of defects, pores and cracks, thereby effectively optimizing the density and uniformity of the coating, and finally significantly improving the corrosion resistance of the titanium alloy surface.

[0070] Furthermore, the copper element introduced by the present invention has natural antibacterial properties and can effectively inhibit and kill a variety of bacteria, fungi and other microorganisms. Copper ions can destroy the cell walls and cell membranes of microorganisms, causing the leakage of cell contents, thereby inhibiting their growth and reproduction. This property enables the copper-doped coating to reduce the formation of bacteria and biofilms in the marine environment, reducing the risk of biofouling.

[0071] In combination with the first aspect, in some embodiments of the present invention, the particle size of the titanium alloy powder is 40-150 μm.

[0072] In combination with the first aspect, in some embodiments of the present invention, the particle size of the titanium alloy powder is any value of 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or a range formed by any two of them, such as 50 to 140μm.

[0073] In combination with the first aspect, in some embodiments of the present invention, the particle size of the copper powder is 40-150 μm.

[0074] In combination with the first aspect, in some embodiments of the present invention, the particle size of the copper powder is any value of 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or a range formed by any two of them, such as 50-140μm.

[0075] In combination with the first aspect, in some embodiments of the present invention, the titanium alloy powder includes a powder containing a β-phase titanium alloy, or a dual-phase titanium alloy powder containing an α-phase titanium alloy and a β-phase titanium alloy.

[0076] The titanium alloy powder includes powder containing β-phase titanium alloy, or dual-phase titanium alloy powder containing α-phase titanium alloy and β-phase titanium alloy, which can promote the formation of β-phase, change the ratio of α-phase and β-phase, and ultimately effectively improve the density and uniformity of the coating, and improve the corrosion resistance of the titanium alloy surface.

[0077] The titanium alloy powder includes TC4 titanium alloy powder. The element content of TC4 titanium alloy powder is as follows, by mass percentage: Al: 5.5% to 6.75%; V: 3.5% to 4.5%; Fe: ≤0.03%; C: ≤0.08%; O: ≤0.20%; N: ≤0.05%; H: ≤0.015%; other single impurity elements ≤0.01%, the total amount of impurity elements ≤0.05%; the balance is Ti.

[0078] In a second aspect, some embodiments of the present invention provide a method for preparing an anti-fouling and corrosion-resistant coating on the surface of a titanium alloy according to the first aspect of the present invention, comprising the step of laser cladding a titanium-based composite powder on the surface of a titanium alloy substrate.

[0079] It should be noted that compared with traditional antifouling technologies, laser cladding modification technology achieves metallurgical bonding through high-energy-density lasers, which can significantly improve the adhesion between the coating and the substrate, and effectively enhance the long-term application of the coating in the marine environment. Specifically:

[0080] The present invention applies titanium-based composite powder prepared from titanium alloy powder and copper powder to a laser cladding process, thereby obtaining a dense and uniform coating on the surface of the titanium alloy substrate. This coating can effectively improve the corrosion resistance of the titanium alloy, and especially after containing copper elements, the corrosion resistance of the coating is significantly improved.

[0081] The preparation method of the present invention changes the phase composition of the titanium alloy by introducing the copper element, promotes the formation of the β phase, and adjusts the ratio of the α phase to the β phase. The addition of copper makes the grains in the coating more refined, and the uniformity and density are also improved. This optimized microstructure reduces the formation of defects, pores and cracks, thereby improving the overall performance of the coating.

[0082] Furthermore, the preparation method of the present invention effectively optimizes the density and uniformity of the titanium alloy coating by changing the phase composition and microstructure of the alloy, which not only improves the corrosion resistance of the coating, but also enhances the mechanical properties of the coating and prolongs the service life of the coating.

[0083] It should also be noted that the laser cladding process can efficiently deposit titanium-based composite powders onto the surface of titanium alloy substrates, and is simple to operate and has high processing accuracy. Compared with traditional coating technology, laser cladding technology can better control the thickness and quality of the coating, and does not require complex post-processing.

[0084] Therefore, the preparation method of the present invention not only significantly improves the corrosion resistance and anti-fouling ability of the titanium alloy surface, but also enhances its stability and reliability in long-term use by improving the structure and quality of the coating.

[0085] In combination with the second aspect, in some embodiments of the present invention, the method for preparing the anti-fouling and corrosion-resistant coating on the surface of the titanium alloy may be:

[0086] Pre-treating the titanium alloy surface to obtain a pre-treated titanium alloy surface;

[0087] The titanium alloy powder and the copper powder are ball-milled and mixed, and then dried to obtain a titanium-based composite powder;

[0088] The titanium-based composite powder is clad on the surface of the base material by laser cladding to form a titanium-based anti-fouling and corrosion-resistant coating on the surface of the base material;

[0089] After the sample was cooled down to room temperature naturally after cladding, the oxide layer on the surface was removed by an angle grinder, and the surface was rinsed with anhydrous ethanol and dried immediately in preparation for subsequent performance testing.

[0090] in:

[0091] The pretreatment method can be: using a handheld vibrating sandpaper machine (SiC sandpaper) to grind and polish the surface of the titanium alloy to remove surface oil and oxide layer, the grinding and polishing steps end with 800 mesh sandpaper, and the substrate surface is cleaned with anhydrous ethanol and blown dry to obtain the pretreated titanium alloy.

[0092] In combination with the second aspect, in some embodiments of the present invention, the titanium alloy matrix includes a titanium alloy matrix containing a β phase, or a dual-phase titanium alloy matrix containing an α phase and a β phase.

[0093] The titanium alloy matrix includes a titanium alloy matrix containing a β phase, or a dual-phase titanium alloy matrix containing an α phase and a β phase, which can promote the formation of the β phase, change the ratio of the α phase to the β phase, and ultimately effectively improve the density and uniformity of the coating, and enhance the corrosion resistance of the titanium alloy surface. The reasons include:

[0094] The α phase and β phase of titanium alloy have different crystal structures and physical and chemical properties. The α phase is a hexagonal close-packed (HCP) structure, and the β phase is a body-centered cubic (BCC) structure. By changing the composition of the alloy, especially the addition of copper, the formation of the β phase can be promoted. The β phase has a lower density and stronger plasticity than the α phase, which can improve the processability and toughness of the alloy.

[0095] When the titanium alloy matrix itself contains β phase or α+β dual phase, the increase of β phase will significantly affect the microstructure of the coating. Since β phase has a large grain growth ability, it can promote the refinement and homogenization of grains in the coating, reduce pores and cracks in the coating, and thus improve the density of the coating.

[0096] The presence of β phase can make the coating maintain a more uniform molten pool temperature and fluidity during the laser cladding process, which helps the uniform deposition of the coating on the substrate surface, reduces defects in the coating, and enhances the overall uniformity and stability of the coating.

[0097] The addition of copper will affect the ratio of α phase to β phase, because copper as an alloying element can reduce the β transformation temperature of titanium alloy and promote the formation of β phase. This change in phase ratio helps the coating form a more uniform structure.

[0098] Adjusting the ratio of α phase and β phase can optimize the mechanical properties of titanium alloy. β phase is more flexible and has better ductility than α phase, which makes the coating more stable when subjected to external forces and less likely to crack or fall off. In addition, the presence of β phase can effectively improve the corrosion resistance of the coating and enhance its corrosion resistance in harsh environments.

[0099] Improved coating density: With the promotion of the β phase, the grains in the coating can grow more evenly, and due to the lower energy state of the β phase lattice, it can help reduce defects, porosity and cracks in the coating. The dense coating not only has stronger mechanical properties, but also effectively blocks the penetration of corrosive media and improves corrosion resistance.

[0100] The increase of β phase can also improve the corrosion resistance of the coating surface. β phase usually has better oxidation resistance and can effectively inhibit the formation of unfavorable corrosion phases in titanium alloys. The β phase in the titanium alloy coating helps to improve the formation of the passivation film on the surface of the titanium alloy. This passivation film can effectively isolate the corrosive medium and prevent the corrosion of the base metal.

[0101] The introduction of copper not only promotes the formation of β phase, but also enhances the corrosion resistance of the coating. Copper has the characteristics of anti-seawater corrosion and anti-microbial adhesion, so the presence of copper further enhances the anti-fouling and corrosion resistance of the coating.

[0102] During the laser cladding process, the temperature of the coating area varies greatly. The β phase and α+β dual-phase structure in the substrate help control the temperature gradient and phase change process in the molten pool. Rapid cooling after laser cladding may cause part of the α phase in the coating to transform into the β phase. The formation of the β phase helps to form a strong diffusion ability at high temperature, promoting the diffusion of alloying elements (such as copper) between the substrate and the coating, thereby further improving the adhesion and corrosion resistance of the coating.

[0103] Therefore, when the titanium alloy matrix contains β phase or dual-phase structure, by changing the ratio of α phase to β phase, the microstructure optimization of the coating can be promoted, defects can be reduced, and the density and uniformity of the coating can be improved. The increase of β phase not only improves the mechanical properties of the coating, but also significantly improves the corrosion resistance of the titanium alloy surface. At the same time, the introduction of copper element helps to further improve the corrosion resistance and antifouling performance of the coating.

[0104] In combination with the second aspect, in some embodiments of the present invention, the titanium alloy matrix includes α+β dual-phase titanium alloys such as TC4 and TB6 and β-phase titanium alloys such as TB2.

[0105] The titanium alloy powder and the titanium alloy substrate are of the same grade, which can make the bonding strength between the coating and the substrate stronger. The same grade (for example, using the same type of titanium alloy, such as TC4 titanium alloy powder and TC4 titanium alloy substrate) can make the bonding strength between the coating and the substrate stronger. One of the reasons is that the same grade of titanium alloy powder and the substrate usually have similar chemical composition and alloy ratio. This makes the chemical compatibility of the coating and the substrate material better and reduces interface problems caused by composition mismatch. The consistency of the alloying elements of the titanium alloy (such as aluminum, vanadium, etc.) between the coating and the substrate helps to form a uniform metal bonding layer, reducing thermal stress, strain differences and possible interface brittleness, thereby improving the bonding strength. The second reason is that if the alloy powder and the substrate are of the same grade, their thermal expansion coefficients are similar, which means that the coating expands to the same extent as the substrate in a high temperature environment. This

[0106] In the laser cladding process, the thermal expansion of the coating and the substrate will not produce too large a difference, thereby reducing the problems of cracks and peeling caused by thermal stress, and further enhancing the bonding strength between the coating and the substrate. In addition, titanium alloys of the same grade are usually very close in terms of grain structure, phase composition, grain boundary characteristics, etc. Since the microstructure of the coating and the substrate material is consistent or similar, it is easier for them to form a stable interface through solid-state diffusion or grain boundary bonding, which helps to improve the bonding strength between the coating and the substrate. Further, when the coating and the substrate are of the same grade, the melting and solidification process during the laser cladding process is more uniform, avoiding the interface instability caused by differences in melting points and phase change behaviors between different materials. The interface formed in this way is more stable, which enhances the bonding strength between the coating and the substrate. It should also be noted that if the material properties of the coating and the substrate are similar, especially the crystal structure is similar, then they can be more easily fused during the solidification process, reducing defects (such as cracks, pores, dislocations, etc.) caused by lattice mismatch. These defects usually weaken the bonding strength between the coating and the substrate.

[0107] In combination with the second aspect, in some embodiments of the present invention, the method for preparing the titanium-based composite powder includes the steps of mixing and ball-milling titanium alloy powder and copper powder according to a proportion under a protective atmosphere.

[0108] Ball milling is to make the copper powder evenly distributed in the titanium alloy powder.

[0109] In combination with the second aspect, in some embodiments of the present invention, the ball-to-material ratio of ball milling can be 5:1.

[0110] In combination with the second aspect, in some embodiments of the present invention, the grinding balls are stainless steel grinding balls.

[0111] In combination with the second aspect, in some embodiments of the present invention, the diameter of the grinding ball is 1 mm to 10 mm.

[0112] In combination with the second aspect, in some embodiments of the present invention, the ball milling time is 100 min to 200 min.

[0113] In combination with the second aspect, in some embodiments of the present invention, the ball milling time is any value among 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, 180min, 190min, 200min or a range value formed by any two of them, such as 140min to 160min.

[0114] In combination with the second aspect, in some embodiments of the present invention, the rotation speed of the ball mill is 100 rpm to 200 rpm.

[0115] In combination with the second aspect, in some embodiments of the present invention, the ball mill rotation speed is any value of 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm, 2000rpm or a range formed by any two of them, such as 140rpm to 160rpm.

[0116] After ball milling, the composite powder is dried at 90°C to 110°C for 2 to 4 hours. The purpose of drying is to remove moisture from the powder.

[0117] In combination with the second aspect, in some embodiments of the present invention, the powder feeding method of laser cladding includes coaxial powder feeding or axial powder feeding.

[0118] In combination with the second aspect, in some embodiments of the present invention, the powder feeding rate of laser cladding is 0.5 r / min to 4.5 r / min.

[0119] In combination with the second aspect, in some embodiments of the present invention, the powder feeding rate of laser cladding is any value of 0.5r / min, 1.0r / min, 1.5r / min, 2.0r / min, 2.5r / min, 3.0r / min, 3.5r / min, 4.0r / min or a range formed by any two of them, such as 2.0r / min to 3.0r / min.

[0120] In combination with the second aspect, in some embodiments of the present invention, the laser power of laser cladding is 1200W to 1800W.

[0121] In combination with the second aspect, in some embodiments of the present invention, the laser power of laser cladding is any value among 1300W, 1400W, 1500W, 1600W, 1700W, 1800W or a range formed by any two of them, such as 1400W to 1600W.

[0122] In combination with the second aspect, in some embodiments of the present invention, the scanning rate of laser cladding is 6 mm / s to 10 mm / s.

[0123] In combination with the second aspect, in some embodiments of the present invention, the scanning rate of laser cladding is any value among 6mm / s, 7mm / s, 8mm / s, 9mm / s, 10mm / s or a range formed by any two of them, such as 7mm / s to 9mm / s.

[0124] In combination with the second aspect, in some embodiments of the present invention, the preparation method further includes a step of pretreating the surface of the titanium alloy substrate before laser cladding.

[0125] In conjunction with the second aspect, in some embodiments of the present invention, the preprocessing step includes:

[0126] The titanium alloy surface was polished by hand-held vibrating sandpaper machine (SiC sandpaper) to remove surface oil and oxide layer. The polishing step was ended with 800-mesh sandpaper. The substrate surface was cleaned with anhydrous ethanol and dried for later use.

[0127] In the third aspect, some embodiments of the present invention provide the use of the anti-fouling and corrosion-resistant coating on the surface of the titanium alloy according to the first aspect of the present invention in marine engineering equipment.

[0128] It can be understood that the application of the antifouling and corrosion-resistant coating on the surface of titanium alloy in marine engineering equipment of the present invention has at least the following beneficial effects:

[0129] 1. Excellent seawater corrosion resistance. Seawater in the marine environment contains high concentrations of salt and a variety of corrosive substances. Titanium alloys themselves have good corrosion resistance, but in harsh marine environments, the risk of corrosion of titanium alloys still exists. By applying anti-fouling and corrosion-resistant coatings on the surface of titanium alloys, especially titanium-based composite powder coatings with copper elements, their resistance to seawater corrosion can be further improved. The density and uniformity of the coating can effectively prevent the penetration of salt water and other corrosive media, thereby reducing the corrosion problems of marine engineering equipment and extending the service life of the equipment.

[0130] 2. Antifouling performance. Dirt, seaweed, microorganisms and other biological attachments in the marine environment often adhere to the surface of marine engineering equipment, causing the surface performance of the equipment to deteriorate and even affecting the operating efficiency of the equipment. The antifouling coating changes the microstructure of the titanium alloy surface to make its surface more resistant to adhesion. The surface of the coating can reduce the contact force between biological attachments and the metal surface, reduce the accumulation of attachments, thereby keeping the equipment surface clean and smooth, and helping to reduce cleaning and maintenance costs.

[0131] 3. Improve the reliability and safety of equipment. In marine engineering, equipment is usually faced with long-term high-intensity working conditions and complex environmental factors. After the titanium alloy surface is protected by anti-fouling and corrosion-resistant coating, it can effectively reduce the risk of failure caused by corrosion and biological adhesion. The excellent performance of the coating improves the reliability of the equipment, reduces the maintenance frequency and downtime, and ensures the safe operation of the equipment in the marine environment.

[0132] 4. Reduce maintenance costs. Marine engineering equipment such as ships, platforms, and submarine pipelines are exposed to seawater for a long time and will be affected by corrosion and biological attachment, requiring frequent maintenance and cleaning. After using titanium alloy surface anti-fouling and corrosion-resistant coating, the equipment surface is easier to keep clean, and the accumulation of corrosion and attachments is effectively controlled, thereby reducing the frequency of repairs and cleaning and significantly reducing maintenance costs.

[0133] 5. Enhance long-term stability and environmental adaptability. The temperature, humidity, tides, surges, etc. in the marine environment are changeable, and marine engineering equipment needs to have strong environmental adaptability. The high density and uniformity of the anti-fouling and corrosion-resistant coating on the surface of titanium alloy enables it to maintain stable performance during long-term use, resist the severe test of the marine environment, and further enhance the adaptability and long-term stability of titanium alloy in complex environments.

[0134] Therefore, the application of the titanium alloy surface anti-fouling and corrosion-resistant coating of the present invention in marine engineering equipment can significantly improve the corrosion resistance of the equipment, reduce dirt adhesion, extend the service life, improve the reliability and safety of the equipment, and reduce maintenance costs. It also has good environmental adaptability and sustainability, and is an effective solution to improve equipment performance, reduce maintenance costs, and extend service life in the field of marine engineering.

[0135] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0136] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0137] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0138] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0139] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0140] In the embodiment, the TC4 titanium alloy powder is commercial Ti6Al4V alloy powder, and the copper powder is commercial copper powder. The particle size of the titanium alloy powder and the copper powder is 40-150 μm.

[0141] Example 1

[0142] An antifouling and corrosion-resistant coating on the surface of a titanium alloy was prepared. The raw material for the preparation was a titanium-based composite powder, which contained Ti6Al4V alloy powder and copper powder. In terms of mass percentage, the content of Ti6Al4V alloy powder in the titanium-based composite powder was 97wt%, and the content of copper powder was 3wt%.

[0143] The preparation method is:

[0144] (1) In a planetary ball mill containing stainless steel grinding balls with a diameter of 5 mm, TC4 titanium alloy powder and copper powder were continuously mixed at a speed of 150 r / min for 150 minutes, and then the mixed powder was dried in an oven at 100° C. for 3 hours to obtain a final titanium-based composite powder, in which the mass content of TC4 titanium alloy powder was 97% and the mass content of copper powder was 3%;

[0145] (2) Using TC4 titanium alloy as the base material, the surface of the base material was polished with SiC sandpaper to remove surface oil and oxide layer, and then the surface of the base material was cleaned with anhydrous ethanol with a purity greater than 99.9%, and immediately dried for use. Subsequently, laser cladding surface modification was performed by coaxial powder feeding to form a titanium-based composite coating on the surface of the TC4 titanium alloy material; the conditions of the laser cladding treatment included: the inert atmosphere environment was an argon environment, the laser power was 1400W, the laser scanning rate was 8mm / s, and the powder feeding rate was 2.5r / min. The obtained sample was named TC4 / TC4-3Cu.

[0146] Example 2

[0147] An antifouling and corrosion-resistant coating on the surface of a titanium alloy was prepared. The raw material for the preparation was a titanium-based composite powder, which contained Ti6Al4V alloy powder and copper powder. In terms of mass percentage, the content of Ti6Al4V alloy powder in the titanium-based composite powder was 95wt%, and the content of copper powder was 5wt%.

[0148] The preparation method is:

[0149] (1) In a planetary ball mill containing stainless steel grinding balls with a diameter of 5 mm, TC4 titanium alloy powder and copper powder were continuously mixed at a speed of 150 r / min for 150 minutes, and then the mixed powder was dried in an oven at 100° C. for 3 hours to obtain a final titanium-based composite powder, in which the mass content of TC4 titanium alloy powder was 95% and the mass content of copper powder was 5%;

[0150] (2) Using TC4 titanium alloy as the base material, the surface of the base material was polished with SiC sandpaper to remove surface oil and oxide layer, and then the surface of the base material was cleaned with anhydrous ethanol with a purity greater than 99.9%, and immediately dried for use. Subsequently, laser cladding surface modification was performed by coaxial powder feeding to form a titanium-based composite coating on the surface of the TC4 titanium alloy material; the conditions of the laser cladding treatment included: the inert atmosphere environment was an argon environment, the laser power was 1400W, the laser scanning rate was 8mm / s, and the powder feeding rate was 2.5r / min. The obtained sample was named TC4 / TC4-5Cu.

[0151] Example 3

[0152] An antifouling and corrosion-resistant coating on the surface of a titanium alloy was prepared. The raw material for the preparation was a titanium-based composite powder, which contained Ti6Al4V alloy powder and copper powder. In terms of mass percentage, the content of Ti6Al4V alloy powder in the titanium-based composite powder was 93wt%, and the content of copper powder was 7wt%.

[0153] The preparation method is:

[0154] (1) In a planetary ball mill with stainless steel grinding balls of 5 mm in diameter, TC4 titanium alloy powder and copper powder were continuously mixed at a speed of 150 r / min for 150 minutes, and then the mixed powder was dried in an oven at 100° C. for 3 hours to obtain a final titanium-based composite powder, in which the mass content of TC4 titanium alloy powder was 93% and the mass content of copper powder was 7%;

[0155] (2) Using TC4 titanium alloy as the base material, the surface of the base material was polished with SiC sandpaper to remove surface oil and oxide layer, and then the surface of the base material was cleaned with anhydrous ethanol with a purity greater than 99.9%, and immediately dried for use. Subsequently, laser cladding surface modification was performed by coaxial powder feeding to form a titanium-based composite coating on the surface of the TC4 titanium alloy material; the conditions of the laser cladding treatment included: the inert atmosphere environment was an argon environment, the laser power was 1400W, the laser scanning rate was 8mm / s, and the powder feeding rate was 2.5r / min. The obtained sample was named TC4 / TC4-7Cu.

[0156] Comparative Example 1

[0157] The titanium alloy surface was polished with a handheld vibrating sandpaper machine (SiC sandpaper) to remove surface oil and oxide layer. The polishing step ended with 800-mesh sandpaper. The substrate surface was cleaned with anhydrous ethanol and dried to obtain the pretreated TC4 titanium alloy.

[0158] Comparative Example 2

[0159] An antifouling and corrosion-resistant coating on the surface of titanium alloy was prepared, which did not contain copper powder.

[0160] The preparation method is:

[0161] (1) drying the TC4 titanium alloy powder in an oven at 100° C. for 3 h to obtain a final powder, wherein the powder contains only the TC4 titanium alloy powder and does not contain copper powder;

[0162] (2) Using TC4 titanium alloy as the base material, the surface of the base material was polished with SiC sandpaper to remove surface oil and oxide layer, and then the surface of the base material was cleaned with anhydrous ethanol with a purity greater than 99.9%, and immediately dried for use. Subsequently, laser cladding surface modification was performed by coaxial powder feeding to form a titanium-based coating on the surface of the TC4 titanium alloy material; the conditions of the laser cladding treatment included: the inert atmosphere environment was an argon environment, the laser power was 1400W, the laser scanning rate was 8mm / s, and the powder feeding rate was 2.5r / min. The obtained sample was named TC4 / TC4.

[0163] Bond strength test

[0164] The tensile strength of the samples of Examples 1 to 3 and Comparative Example 2 was tested by a universal mechanical testing machine in accordance with the Chinese national standard GB / T 8642-2002. The tensile strength of all samples was greater than 80 MPa, indicating that they can maintain high reliability and stability in practical applications. This means that these coatings are not prone to coating shedding or failure under the action of external tensile forces, which is conducive to long-term use.

[0165] The tensile bonding strength of all samples was greater than 80 MPa, indicating that the laser cladding process can effectively combine the titanium-based composite powder with the matrix material, and the density and uniformity of the coating have reached a good level.

[0166] Coatings with a tensile bond strength greater than 80MPa are suitable for a variety of high-demand engineering applications, especially in marine environments, aerospace and other fields. They can ensure that the coating will not peel off when exposed to harsh environments for a long time, thereby ensuring the long-term protective performance of the coating.

[0167] Surface topography test

[0168] The element distribution on the surface of the samples of Examples 1 to 3 was analyzed using a field emission electron microscope and an EDS spectrometer (SU5000, Japan). Figure 1 shown. Figure 1 (a) to (c) are element distribution diagrams of the sample surfaces of Examples 1 to 3, respectively. It can be seen from the diagram that the copper element in the cladding coating is evenly distributed on the sample surface, indicating that a dense and uniform titanium-based composite coating is formed on the titanium alloy surface.

[0169] Phase structure characterization

[0170] The physical structures of the samples of Examples 1 to 3 and Comparative Examples 1 to 2 were characterized by an X-ray diffractometer (BRUKER, USA). During the test, a Cu-Kα target (λ = 0.15406 nm) was used, the test voltage and current were 40 kV and 40 mA, respectively, the test range was 20 to 80°, the step length was 0.02°, and the rate was 5° / min. The characterization results are shown in Figure 2. Figure 2 As shown in the figure, after adding Cu element, the microstructure of titanium alloy changes significantly, and the precipitation phase Ti2Cu appears. With the increase of copper content, the diffraction peak intensity of Ti2Cu becomes larger.

[0171] Microhardness test

[0172] The microhardness of the samples of Examples 1 to 3 and Comparative Examples 1 to 2 was tested using a microhardness tester (HVS-1000, China) with an HV indenter, a test force of 100 gf, and a force holding time of 10 s. The test results are shown in Table 1. Figure 3 As shown, compared with Comparative Example 1, the surface microhardness of Comparative Example 2 and Examples 1 to 3 is significantly increased, among which Comparative Example 2 and Example 3 have the maximum microhardness of 498 HV and 483.77 HV, indicating that the increase in the mass content of copper powder in the laser cladding layer composite powder can effectively improve the microhardness of the TC4 titanium alloy surface.

[0173] Corrosion resistance test

[0174] Electrochemical experiments were performed in a conventional three-electrode system using an electrochemical workstation to evaluate the corrosion resistance of the samples. The original and modified titanium alloy samples were polished with 400, 800, and 1000# sandpapers in turn, and then cured and packaged with epoxy resin at room temperature. Copper wires were welded on the back, and the cured titanium alloy samples were polished to a mirror surface, forming an area of ​​1.0 cm 2 work surface.

[0175] In the electrochemical experiment, a platinum sheet electrode (10mm×10mm×0.1mm) was used as an auxiliary electrode, an Ag / AgCl electrode was used as a reference electrode, the sample to be tested was used as a working electrode, and the test electrolyte was an artificial seawater solution prepared according to the national standard GB / T 6682-2008. All electrochemical measurements were performed after the open circuit potential (OCP) was stabilized for at least 3600s. Electrochemical impedance spectroscopy (EIS) measurements were performed at a 5mV amplitude sinusoidal voltage in the frequency range of 100kHz to 0.01Hz, and the results were analyzed and fitted using ZsimpWin software. In the potentiodynamic polarization test, polarization curves were tested at a scanning rate of 0.5mV / s in the potential range of -0.3V (vs.OCP) to 1.5V (vs.Ref), and the self-corrosion potential and self-corrosion current density of the samples of Comparative Examples 1 to 2 and the samples prepared in Examples 1 to 3 were obtained by Tafel extrapolation.

[0176] The electrochemical impedance spectroscopy data were fitted with an appropriate equivalent circuit using ZsimpWin software. The equivalent circuit diagram is shown in Figure 4 As shown, the specific fitting parameters of each component in the fitting circuit are shown in Table 1.

[0177] Table 1

[0178]

[0179]

[0180] Equivalent Circuit R s (Q1R1)(Q2R2) is used to simulate the EIS data of the samples of Comparative Examples 1-2 and Examples 1-3. Considering the surface inhomogeneity and dispersion effect, a constant phase angle element (CPE) Q is used to replace the ideal capacitor C, where R s represents the solution resistance, R1 and Q1 represent the charge transfer resistance and double layer capacitance, and R2 and Q2 represent the coating resistance and coating capacitance of the composite coating on the titanium alloy surface.

[0181] The polarization resistance value Rp (approximately equal to R1+R2) is an important parameter to measure the degree of corrosion during the corrosion process, and its value is negatively correlated with the corrosion rate. The fitting results show that the sample prepared in comparative example 2 has the smallest Rp value, which is about 2.1×10 5 Ωcm 2 , followed by the sample prepared in comparative example 1, with an Rp value of about 2.5×10 5 Ωcm 2 This is attributed to the fact that a large number of secondary α phase grains are formed during the cooling process of the sample prepared in Comparative Example 2 due to the martensitic phase transformation. In the electrochemical test, many crystal structure defects are easily generated at the secondary α phase grain boundaries. These defects are unevenly distributed along the grain boundaries, causing the grain boundary area to increase, which has a negative impact on the electrochemical behavior of the titanium alloy.

[0182] The titanium alloy sample prepared in Example 2 has the largest R p value, about 16.35×10 5 Ωcm 2 , and with the increase of copper content, R p The value shows a trend of increasing first and then decreasing, which is attributed to the difference in electrode potential between Cu and Ti in the titanium-based composite coating. The presence of Cu reduces the anodic dissolution rate of the titanium alloy in the corrosive environment and slows down the electrochemical corrosion process. However, with the addition of copper content, the volume fraction of the α phase in the titanium-based composite coating decreases significantly, while the sum of the volume fractions of the β and Ti2Cu phases increases significantly. Therefore, the significant increase in the cathode area leads to the strengthening of the galvanic corrosion between different phases, thereby reducing the corrosion resistance of the titanium alloy surface.

[0183] Figure 5 Table 2 shows the polarization curves of the comparative sample and the samples prepared in Examples 1 to 3. Table 3 shows the electrochemical parameters obtained by fitting the polarization curves.

[0184] Table 2

[0185] sample <![CDATA[E corr / V]]> <![CDATA[i corr / nA cm -2 ]]> Comparative Example 1 -0.254±0.014 272±11 Comparative Example 2 -0.284±0.011 349±16 Example 1 -0.162±0.006 48.6±1.4 Example 2 -0.0718±0.005 39.2±2.2 Example 3 -0.16±0.004 65.1±1.9

[0186] The results show that the sample prepared in Example 2 has the smallest self-corrosion current density. The lower the value of the self-corrosion current density, the slower the corrosion rate of the material and the better the corrosion resistance. In addition, with the increase of copper content, the self-corrosion current density shows a trend of first decreasing and then increasing, but the self-corrosion current density is significantly lower than that of the comparative example.

[0187] In summary, the polarization resistance values ​​R of the samples prepared in Examples 1 to 3 are p The self-corrosion current density is significantly greater than that of the comparative sample, and the self-corrosion current density is significantly less than that of the comparative sample, indicating that the composite coating can effectively improve the corrosion resistance of the titanium alloy surface. The addition of a small amount of copper element in the titanium-based composite coating helps to form a more dense and uniform surface layer structure, making it more difficult for the corrosive medium to penetrate into the metal, thereby improving the corrosion resistance of the titanium alloy surface. As the copper content increases, it may cause electrochemical inhomogeneity between different phases on the titanium alloy surface, forming micro-galvanic corrosion and reducing the overall corrosion resistance.

[0188] The results show that the copper powder has the beneficial effects of the present invention when the mass content of the copper powder is within 3% to 7%, and has the most beneficial effect of corrosion resistance when the mass content of the copper powder is 5%.

[0189] Antibacterial performance test

[0190] Antibacterial tests were performed on the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 2. Pseudomonas aeruginosa, a common Gram-negative bacterium in the ocean, was selected as the target fouling organism, and Pseudomonas aeruginosa was proliferated and cultured using 2216E liquid culture medium on a shaker (30°C, 130 r / min). After 24 hours, the cultured bacterial solution was diluted 1:100.

[0191] Then, the prepared samples were immersed in the diluted bacterial culture solution and incubated for 36 h. The samples were taken out and washed with PBS buffer after being immersed in the bacterial solution.

[0192] The cleaned samples were immersed in 2.5% glutaraldehyde solution at -4°C for 4 hours, graded diluted with alcohol, and dried in a vacuum drying oven for 24 hours before being used for scanning electron microscopy observation to conduct a qualitative analysis of bacterial adhesion on the sample surface before and after modification.

[0193] Figure 6 The graphs are of bacteria adhesion on the surfaces of the samples prepared in the comparative examples and Examples 1 to 3. The experimental results show that a large number of Pseudomonas aeruginosa are attached to the surfaces of the samples prepared in Examples 1 to 2 ( Figure 6 (a) and (b)), however, with the addition of copper, the number of Pseudomonas aeruginosa attached to the surface of the samples prepared in Examples 1 to 3 was significantly reduced, and the morphology of the attached bacteria changed significantly, with wrinkles and defects on the bacteria ( Figure 6 (c) to (e) in the figure.

[0194] The antifouling mechanism of composite coating is as follows Figure 7 As shown, the copper ions in the coating can interact with the components of the bacterial cell wall, causing the destruction of the cell wall structure, thereby causing the cell membrane to lose integrity. This destruction can lead to the leakage of cell contents and cause bacterial death, thereby reducing the adhesion of bacteria on the titanium alloy surface.

[0195] The beneficial effects of the present invention are achieved when the mass content of the copper powder is within 3% to 7%.

[0196] Anti-biofilm performance test

[0197] The cultured and proliferated Pseudomonas aeruginosa bacterial solution was diluted at a ratio of 1:100, and after shaking evenly, the diluted bacterial solution was added to the 24-well bacterial culture plate (1 mL / well) where the samples of Examples 1 to 3 and Comparative Examples 1 to 2 were placed. The culture plate was sealed and placed in a shaker at 37°C for 24 hours. After the culture was completed, the sample was taken out and the sample surface was rinsed with sterile PBS buffer to remove bacteria that were not firmly attached. Then, the sample surface was stained with a 0.1% crystal violet solution for 15 minutes (500 μL per well). After staining, the sample surface was rinsed with sterile PBS buffer again until the last washing solution had no obvious color. The sample was placed in a clean bench to dry, and the dried sample was soaked in a 30% glacial acetic acid solution for 15 minutes, and the washing solution was collected. The optical density (OD590) value of the washing solution at 590 nm was measured using a UV-visible spectrophotometer. The size of the OD value is proportional to the amount of biofilm. The higher the OD value, the more biofilm the bacteria generate on the surface of the material.

[0198] Figure 8 It is the absorbance value of the eluate OD 590nm on the surface of different samples. The results show that compared with the comparative example, Examples 1 to 3 all exhibit an anti-biofilm rate of more than 68%. The addition of copper element can effectively inhibit the proliferation of bacteria on the surface of titanium alloy, thereby reducing the formation of biofilm.

[0199] In summary, the present invention provides an anti-fouling and corrosion-resistant coating with high efficiency and strong stability. The anti-fouling and corrosion-resistant coating is metallurgically bonded to the surface of titanium alloy through surface modification by laser cladding, and the introduction of copper element effectively improves the antibacterial and corrosion resistance of the coating, and can significantly inhibit the attachment of microorganisms and the formation of biofilm.

[0200] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A titanium alloy surface antifouling and corrosion resistant coating, characterized in that: The preparation raw materials include titanium-based composite powder, which includes titanium alloy powder and copper powder. In terms of mass percentage, the content of the titanium alloy powder in the titanium-based composite powder is 93wt% to 97wt%, and the content of the copper powder in the titanium-based composite powder is 3wt% to 7wt%.

2. The antifouling and corrosion-resistant coating on the titanium alloy surface according to claim 1, characterized in that: The particle size of the titanium alloy powder is 40 to 150 μm; and / or the particle size of the copper powder is 40 to 150 μm.

3. The antifouling and corrosion-resistant coating on the titanium alloy surface according to claim 1 or 2, characterized in that: The titanium alloy powder includes a powder containing a β-phase titanium alloy, or a dual-phase titanium alloy powder containing an α-phase titanium alloy and a β-phase titanium alloy.

4. A method for preparing an antifouling and corrosion-resistant coating on a titanium alloy surface as claimed in any one of claims 1 to 3, characterized in that: The method comprises the step of laser cladding the titanium-based composite powder on the surface of a titanium alloy substrate.

5. The method according to claim 4, characterized in that The titanium alloy matrix includes a titanium alloy matrix containing a β phase, or a dual-phase titanium alloy matrix containing an α phase and a β phase; and / or, the titanium alloy powder and the titanium alloy matrix are of the same grade.

6. The method according to claim 4, characterized in that The preparation method of the titanium-based composite powder comprises the steps of mixing and ball-milling the titanium alloy powder and the copper powder according to a proportion under a protective atmosphere.

7. The method according to claim 6, characterized in that The ball-to-material ratio of the ball mill is 3 to 6:1; and / or the ball milling time is 100 min to 200 min; and / or the ball milling speed is 100 rpm to 200 rpm.

8. The method according to claim 4, characterized in that The powder feeding method of the laser cladding includes coaxial powder feeding or axial powder feeding; and / or, the powder feeding rate of the laser cladding is 0.5r / min~4.5r / min; and / or, the laser power of the laser cladding is 1200W~1800W; and / or, the scanning rate of the laser cladding is 6mm / s~10mm / s.

9. The method according to any one of claims 4 to 8, characterized in that The method also includes the step of pre-treating the surface of the titanium alloy substrate before laser cladding.

10. Use of the antifouling and corrosion-resistant coating on the surface of titanium alloy according to any one of claims 1 to 3 in marine engineering equipment.

Citation Information

Patent Citations

  • Method for manufacturing high-performance medical metal by mixing selective laser melting and laser surface texture

    CN113732307A

  • Metallurgical bonding steel surface composite titanium alloy coating and preparation method thereof

    CN116043214A

  • Cu-containing titanium alloy wear-resistant coating and preparation method thereof

    CN116695114A

Cited By

  • Metal-based self-polishing antifouling composite material, coating and preparation method of metal-based self-polishing antifouling composite material

    CN121293797A

  • A metal-based self-polishing antifouling composite material, coating and method for preparing the same

    CN121293797B